Potential effect of sodium thiosulfate in calciphylaxis: remission of intractable pain - Canlin Yang; Yuqiu Liu; Haifeng Ni; Xiaomin Li; Hong Liu; Xiaoliang Zhang (Journal of the Pakistan Medical Association, 2020)
Abstract Calciphylaxis, a rare disease mainly seen in patients with chronic kidney disease, is characterised by ischaemic skin damages and excruciating pain. Calciphylaxis has poor prognosis which often results in amputation and high mortality. Although guidelines for the management of calciphylaxis are not available, sodium thiosulfate has showed efficacy in many clinical reports. We report the case of a 64-year-old advanced calciphylaxis male patient who had two amputations due to intolerable pain manifested as deteriorating ulcer. After he was treated with intravenous sodium thiosulfate (STS), his pain was significantly relieved with a healing trend of the big wound. One more amputation for the remission of intractable pain was avoided. The treatment experience indicates that sodium thiosulfate is of great value in quick pain relief and reducing suffering of calciphylaxis patients. Keywords: Calciphylaxis, Calcific uremic arteriolopathy, Painful skin ulcer, Maintenance haemodialysis, Continuous....